The Long-Term Impact of Children's Disabilities on Families - Snaebjorn Gunnsteinsson; Herdis Steingrimsdottir (Copenhagen Business School (CBS), Department of Economics, 2019)
Childhood disability is a major health shock that affects parents early in their working life. We estimate its impact on parents' career trajectories, their balance sheets, and major life decisions using detailed register data from Denmark. To identify the causal effect of childhood disability we use an event study approach, where we control for a rich set of pre-birth variables and focus on conditions that have no or weak associations with socioeconomic determinants. We find that having a child with a disability has strong negative impact on mothers' earnings. The effect is persistent and the wage penalty appears to grow over time. Fathers' earnings are also affected but the impact is notably smaller. We find that both parents are less likely to be employed in the long run and are less likely to ascend to top executive positions. The long-term structure of the household is also affected as subsequent fertility is lower and partnership dissolution is more common. Finally, despite this financial shock, long term net worth of families is not affected or may be positively affected, potentially due to help from government transfers and lower cost associated with having fewer other children, or due to a stronger savings motive for the long term care of the disabled child.
hdl:10398/9745
Keywords: E24; I14; J13; J31; 330; disability; children; child; insurance; earnings; income; labor force participation; fertility